2020
DOI: 10.1136/bmjopen-2020-040575
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate exposure to patient presentations on the acute medical placement: a prospective study in a London teaching hospital

Abstract: ObjectivesTo identify the availability and variability of learning opportunities through patient presentations on an acute medical placement at a teaching hospital.DesignA prospective study evaluating all acute admissions to the Acute Medical Unit over 14 days (336 hours). Clinical presentations and the day and time of admission were recorded and compared with the learning outcomes specified in the medical school curriculum.SettingAn Acute Medical Unit at a London teaching hospital.Outcomes(1) Number of clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…For example, Fung et al found that only 23.4% of acute presentations are admitted during normal working hours. 4 This means that more than 75% of acute cases are not encountered by medical students during regular placement hours which, therefore, cannot be incorporated into question making during QBCLs. Students may be deprived of the opportunity to create questions based on crucially important conditions, leading to large gaps in their knowledge and suboptimal performance in both examinations and their clinical career.…”
Section: Dear Editormentioning
confidence: 99%
“…For example, Fung et al found that only 23.4% of acute presentations are admitted during normal working hours. 4 This means that more than 75% of acute cases are not encountered by medical students during regular placement hours which, therefore, cannot be incorporated into question making during QBCLs. Students may be deprived of the opportunity to create questions based on crucially important conditions, leading to large gaps in their knowledge and suboptimal performance in both examinations and their clinical career.…”
Section: Dear Editormentioning
confidence: 99%
“…Students’ limited exposure to clinical presentations in-hours 2 highlights the need to increase scheduled out-of-hours and community-based placements (eg urgent care centres), rather than substituting real-life clinical exposure with pre-written case studies. Instead of relying predominantly on in-hours placement activities, perhaps medical students should have regular out-of-hours patient exposure to enhance their preparedness for practice.…”
Section: Dear Editormentioning
confidence: 99%